Pharmacomodulations around an anti-Alzheimer drug-candidate - Sylvain Marc; Christophe Mésangeau; Mathilde Coevoet; Amélie Barczyk; Stéphane Burlet; Philippe Verwaerde; Cecilia Estrella; Cyrille Brantis; Nicolas Sergeant; Pascal Carato; Patricia Melnyk (Elsevier, 2022)
Alzheimer's disease is a complex and multifactorial disease characterized by extracellular Aβ peptide deposits related to the deregulation of APP metabolism, intracellular aggregation of hyper and abnormally phosphorylated isoforms of Tau proteins, cell death and neuroinflammation. Targeting all these hallmarks at the same time is an interesting strategy for the treatment of this disease. Ezeprogind (AZP2006) is a drug candidate able to correct APP metabolism and interfere with Tau pathology development that is currently in clinical phase 2a for the treatment of tauopathy Progressive Supranuclear Palsy (PSP). In order to decipher the structure-activity relationships, we synthetized 13 analogs and pharmacomodulated different moieties of the scaffold including substitution of the benzimidazole ring and modification of the piperazine central core. APP metabolism was first evaluated with these molecules. Most of them showed no cytotoxicity on SH-SY5Y-APPwt cells and an activity comparable to ezeprogind as reduction of Aβ secretion, increase expression of carboxy-terminal fragments of APP at the micromolar range. Despite major structural differences, most of these analogs showed similar effects on the metabolism of APP. Noteworthy, none of them showed increased efficacy when compared to ezeprogind in vitro. Analogs with different central cores were then tested on primary cortical neurons co-cultured with microglia and injured with Aβ1-42 to analyse Tau metabolism, neuroprotection and neuroinflammation. Together, ezeprogind was shown herein to be the only molecule remaining effective on neuroprotection and neuroinflammation as well as Tau and APP metabolism.